Unawareness, beliefs and speculative trade - Aviad Heifetz; Martin Meier; Burkhard C. Schipper (University of California, Department of Economics, 2009)
We define a generalized state-space model with interactive unawareness and probabilistic beliefs. Such models are desirable for potential applications of asymmetric unawareness. We compare unawareness with probability zero belief. Applying our unawareness belief structures, we show that the common prior assumption is too weak to rule out speculative trade in all states. Yet, we prove a generalized No-trade theorem according to which there can not be common certainty of strict preference to trade. Moreover, we show a generalization of the No-agreeing-to-disagree theorem.
Keywords: C70; C72; D80; D82; 330; unawareness; awareness; zero probability; type-space; common prior; agreement; speculative trade; interactive epistemology